Andexanet Alfa Versus Prothrombin Complex Concentrates/Blood Products as Apixaban/Rivaroxaban Reversal Agents: A Survey Among Pediatric Hematologists. (March 2022) - Rodriguez, Vilmarie; Stanek, Joseph; Kerlin, Bryce A.; Dunn, Amy L.
Direct oral factor Xa inhibitors (DXIs) are approved for use in adult patients with non-valvular heart disease for stroke prevention, and the treatment/prevention of venous thromboembolism (VTE). Recent pediatric clinical trials have demonstrated safety and efficacy of direct oral anticoagulants (DOACs) in the treatment of VTE. However, there is a lack of evidence regarding the use of andexanet alfa and prothrombin complex concentrates (PCC) for anticoagulation reversal of DXIs in the pediatric population. To better understand current DXI reversal strategies in this age group, a 10-question survey was conducted among pediatric hematology members of the Hemostasis and Thrombosis Research Society. Seventeen percent completed the survey (27 of 163 pediatric hematology members) with 74% ( n  = 20) reporting their use of DXIs for the treatment and prevention of VTE. Forty-four percent ( n  = 12) would choose andexanet alfa as first-line treatment for life-threatening bleeding while 52% ( n  = 14) would use PCC first with one individual choosing recombinant factor VII for DXI reversal. Clinical studies of andexanet alfa and PCC for the management of DXI-associated life-threatening bleeding require further investigation in the pediatric population.